The Migraine-Anxiety Comorbidity Among Migraineurs: A Systematic Review - Karimi, Leila; Wijeratne, Tissa; Crewther, Sheila Gillard; Evans, Andrew E.; Ebaid, Deena; Khalil, Hanan (Frontiers in Neurology, 2021)
Background Migraine is recognized as a neurological condition that is often associated with comorbid psychiatric symptoms such as anxiety, depression, bipolar disorder and/or panic disorder. Previous studies have shown that there is a link between migraine and psychiatric disorders. Though some studies have demonstrated the link between migraine and anxiety disorders, there are no systematic reviews that have been published in this area to summarise the evidence. The aim of the present study is to systematically review and meta-analyse the literature associated with comorbidity of migraine and anxiety disorders among migraineurs compared to non-migraineurs. Methods The present systematic review included population-based, cohort and cross-sectional studies if they were reporting the frequency of migraine with either anxiety or depression as diagnosed by a medical practitioner according to the International Classification of Headache Disorders (ICHD-2/3). Results Eight eligible studies from 2060 relevant citations were included in the review. All participants were migraine patients from both primary care and outpatient settings, as well as tertiary headache and anxiety centres, and were compared to non-migraineurs. The results of both the systematic review and meta-analysis showed that there is a strong and consistent relationship between migraine and anxiety. Indeed, the meta-analysis demonstrated that the co-morbidity incidence of co-occurrence for migraine and anxiety has an average OR of 2.33 (2.20-2.47) 3.64 (2.38-5.57)among the prevalence and cross sectional studies and an average RR of 1.63 (1.37-1.93) for two cohort studies; around four times higher in migraine patients compared to non-migraineurs. The major limitations of included studies were small sample sizes and a lack of adjusting of confounding factors. Conclusion The results highlight the need for inclusion of an anxiety screening tool during initial assessments of migraine patients by medical practitioners and/or physicians and may explain why some anxiolytic medications work better than others for migraine mitigation.